Luca Ozzano. 2020. The Masks of the Political God: Religion and Political Parties in Contemporary Democracies. ECPR Press/Rowman & Littlefield. 259pp.s - Driessen, Michael D. (PARTECIPAZIONE E CONFLITTO, 2022)
For Book Review abstract i not required